On the number of critical submanifolds of a function on a manifold - Bondar', O. P. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
We consider differentiable functions on a manifold such that the set of their critical points is a disconnected union of smooth submanifolds. A topological characteristic of the manifold is introduced; in terms of this characteristic, we estimate the least possible number of critical submanifolds of these functions.